Innovative Medicine 2015
DOI: 10.1007/978-4-431-55651-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Immunoreceptors on Mast Cells in Allergy and Inflammation

Abstract: Activation of immune cells is regulated by positive and negative signals triggered by activating and inhibitory cell surface immunoreceptors, respectively. Inhibitory receptors are characterized by the immunoreceptor tyrosine-based inhibition motif (ITIM) in their cytoplasmic domains and play an important role in immune regulation by both lymphoid and myeloid cells. Mast cells express the high-affi nity receptor for IgE (FcεRI) and toll-like receptors (TLR) on the cell surface, and play a central role in aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Exposure of allergic individuals to allergen results in its binding to and ligation of the IgE/FcεRI receptor complex on mast cells, resulting in degranulation and production of cytokines that lead to allergic symptoms and potentially severe anaphylaxis. Since anti-IgE also binds to and ligates the IgE/FcεRI complex, it can behave as a surrogate allergen inducing degranulation and IgE-mediated systemic anaphylaxis when administered to animals. , Mast cells are also known to express a variety of inhibitory receptors including Siglecs that bear the characteristic ITIMs in their cytoplasmic domains. ,,− Using various approaches, several groups have demonstrated that enforced recruitment of inhibitory receptors to the IgE/FcεRI complex can suppress FcεRI-mediated mast cell activation. ,,, In particular, we found that co-presentation of an allergen and a high affinity ligand of CD33 on liposomal nanoparticles (STALs) resulted in suppressed allergen-mediated activation of human mast cells and mast cells from transgenic mice expressing human CD33 . Based on these observations, we set out to conjugate CD33L to anti-IgE to assess its ability to suppress IgE/FcεRI complex-mediated mast cell activation (Figure B).…”
Section: Resultsmentioning
confidence: 83%
“…Exposure of allergic individuals to allergen results in its binding to and ligation of the IgE/FcεRI receptor complex on mast cells, resulting in degranulation and production of cytokines that lead to allergic symptoms and potentially severe anaphylaxis. Since anti-IgE also binds to and ligates the IgE/FcεRI complex, it can behave as a surrogate allergen inducing degranulation and IgE-mediated systemic anaphylaxis when administered to animals. , Mast cells are also known to express a variety of inhibitory receptors including Siglecs that bear the characteristic ITIMs in their cytoplasmic domains. ,,− Using various approaches, several groups have demonstrated that enforced recruitment of inhibitory receptors to the IgE/FcεRI complex can suppress FcεRI-mediated mast cell activation. ,,, In particular, we found that co-presentation of an allergen and a high affinity ligand of CD33 on liposomal nanoparticles (STALs) resulted in suppressed allergen-mediated activation of human mast cells and mast cells from transgenic mice expressing human CD33 . Based on these observations, we set out to conjugate CD33L to anti-IgE to assess its ability to suppress IgE/FcεRI complex-mediated mast cell activation (Figure B).…”
Section: Resultsmentioning
confidence: 83%
“…In the parietal subregion, NMSEW + adult stress resulted in reduced activation levels in males, which was surprising since we had hypothesized that NMSEW would result in overall hyperactivation of mast cells. Currently we don’t know what mechanism is underlying this response, but it could be mediated by male biased, stress-induced local upregulation of mast cell inhibitors such as corticotropin-releasing factor receptor subtype 2 ( D’Costa, 2018 ) or other inhibitory immunoglobulin-like receptors such as Allergin-1 and CD300a ( Shibuya et al, 2015 ). Future studies are needed to identify subpopulation-specific mechanisms of mast cell regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of small clusters of myelinated nerve fibers is the morphological characteristic observed in the recovery of the nerve crush-type lesion (axonotmesis) [61–65]. The presence of mast cells, which are cells associated with allergic and non-allergic inflammatory reactions [66, 67] in nerve samples from F1 group animals could raise the suspected allergic reactions associated with protein extracted from the latex. Notwithstanding, the same cells were also observed in injured animals without the application of the protein.…”
Section: Discussionmentioning
confidence: 99%